The effect of heat treatment on temperature-dependent transport and magnetoresistance in polyacrylonitrile-based carbon fibers - 박민; 장다원; Endo M.; 이성호; 이동수 (Elsevier BV, 2022)
The effects of heat treatment temperatures from 1000 to 2700 °C on the structural, chemical, and mechanical properties of polyacrylonitrile-based carbon fibers (CFs) were investigated. Structural changes affected mechanical properties, and in particular, a higher sp3 content induced a higher tensile strength below 1600 °C. For a comprehensive study on the heat treatment effect and the mechanism for developing high-strength CFs, electrical transport properties were measured for the CFs. The transport behaviors in temperature-dependent conductivity and magnetoresistance were also significantly modified, which led to crossover from strong localization to weak localization due to sp2 carbon ordering. Interestingly, in samples that were subjected to intermediate heat treatment temperatures ranging from 1100 to 1600 °C, anomalous metallic temperature-dependent behavior was observed at low temperatures of below 40 K. This unusual charge transport was analyzed further with a pertinent heterogeneous model employing three-dimensional variable range hopping, weak localization, and linear metallic transport. The results suggest that mixed noncrystalline and crystalline structures with sp2/sp3 carbons, oxygen, and quaternary N groups in CFs enabled the transition behavior at such low temperatures.